Mind mapping: Improving learning outcomes, participation and student creativity in science lessons at SDN 03 Kanigoro - Sari, Maya Kartika; Muaini, Muaini (CAHAYA PENDIDIKAN, 2024)
This research aims to analyze the increase in learning outcomes, student participation, and student creativity in science and science subjects through the Mind Mapping method at SD Negeri 03 Kanigoro Madiun. This type of research uses classroom action research. This research consists of 2 cycles of planning, implementation, observation, and reflection. The research subjects were 27 class IV students. The IPAS material used is "human needs" for cycle I and "money as a means of payment" for cycle II. Data collection techniques using observation, tests and documentation. Data analysis techniques use quantitative data (tests) and qualitative data (non-tests through observation). The success indicator for this research for the test to reach the KKM is 75. The results of participation and creativity are measured from the results of observations in the form of percentages, with success criteria above 76%. The research results showed that the average student learning outcome from pre-research was 67, in cycle I with an average of 72, and in cycle II, the average learning outcome value rose to 84. There was an increase in student learning participation from pre-research at 60%, cycle I was 72%, and cycle II at 85%. Increased student creativity has increased, as seen from pre-research at 70%, cycle I at 75%, and cycle II at 90%. Based on the results of this research, it can be concluded that the mind-mapping learning method can improve learning outcomes, learning participation, and student creativity.